Experiences and opinions of adults with type 1 diabetes on the android-based open-source closed-loop system in China: a qualitative study - Chaofan Wang; Daizhi Yang; Jinhua Yan; Ping Ling; Mengyun Lei; Ying Ni; Xiaodi Guo; Qingying Huang (BMJ Open)
Objective As an emerging technology, Android-based open-source closed-loop system also called Android Artificial Pancreas System (AAPS), has been increasingly validated by evidence for its effectiveness in improving glycaemic outcomes, positioning it as a crucial option for managing type 1 diabetes (T1D). However, there are still only a few studies examining the experiences of using AAPS, and relevant qualitative studies have not been conducted in Asia so far. This study aimed to explore the experiences and opinions of adult patients with T1D on the AAPS.Design Semi-structured interviews and the Insulin Dosing Systems: Perceptions, Ideas, Reflections and Expectations questionnaires were conducted among patients. The questionnaire was scored on a 100-point scale. Thematic analysis was adopted to analyse the transcribed text. Recruitment of interviewees would be halted when no new themes emerged. The scores of the questionnaire on AAPS satisfaction were calculated, and the Mann-Whitney U test was used to compare the results of different sections of the questionnaire.Setting Guangdong Province in China.Participants This study recruited patients with T1D from the Guangdong T1D translational medicine study and the ‘Tang Tang Quan’ T1D online community in China, who participated in a clinical trial on the efficacy and safety of AAPS.Results The study interviewed 20 adults with T1D aged 32±9.94 years. The T1D duration was 10.93±6.26 years and the glycated haemoglobin was 7.38±0.53%. Five main themes were identified: (1) expectations and feedback on AAPS; (2) impact on quality of life; (3) impact on blood glucose management; (4) user experiences; (5) suggestions for AAPS. The average score of AAPS satisfaction was 73.69 (65.94, 85.94). Mann-Whitney U test suggested that the satisfaction derived from glucose management with AAPS surpassed the satisfaction attributed to the enhancement of their overall quality of life (p<0.05).Conclusions Adults with T1D had generally positive experiences with AAPS. The future focus of AAPS research and development should be on optimising glycaemic management, improving device experience and reducing costs.Trial registration number NCT05726461; Pre-results.